189k views
16 votes
Help ASAP!!!!!!! 20 points!!! Simplify the expression

7a^4b^-5 x 2a^2b

User Matt Dodge
by
5.4k points

1 Answer

10 votes

Answer:-


\longrightarrow \sf \: 14a^6b^(-4)

Solution:-


\begin{gathered}\\\implies\quad \sf 7a^4b^(-5) *2a^2b \\\end{gathered}


\begin{gathered}\\\implies\quad \sf 7* a^4* b^(-5) *2* a^2* b \\\end{gathered}

Grouping the like terms


\begin{gathered}\\\implies\quad \sf (7*2)* (a^4* a^2)*(b^(-5) * b )\\\end{gathered}


\begin{gathered}\\\implies\quad \sf 14* a^(4+2)* b^(-5+1) \\\end{gathered}


\begin{gathered}\\\implies\quad \sf 14* a^6* b^(-4)\\\end{gathered}


\begin{gathered}\\\implies\quad \sf 14a^6b^(-4) \\\end{gathered}

User Matveytn
by
5.3k points